2012
DOI: 10.1371/journal.pone.0049290
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes of Blood ACE in Chronic Uremia

Abstract: BackgroundThe pattern of binding of monoclonal antibodies (mAbs) to 16 epitopes on human angiotensin I-converting enzyme (ACE) comprise a conformational ACE fingerprint and is a sensitive marker of subtle protein conformational changes.HypothesisToxic substances in the blood of patients with uremia due to End Stage Renal Disease (ESRD) can induce local conformational changes in the ACE protein globule and alter the efficacy of ACE inhibitors.Methodology/Principal FindingsThe recognition of ACE by 16 mAbs to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 78 publications
1
33
0
Order By: Relevance
“…To our knowledge, this is the first report demonstrating uremic elevation of mACE-expression in relation to pro-atherogenic behaviour of primary human monocytes or THP-1 cells. Such a potential of ACE was previously reported in animal and cell culture models but was not directly correlated with influences of uremia on human monocytes in vitro [26], [27], [28], [29]. With regards to other cell culture systems, it has been demonstrated that uremic toxins may affect oxidative burst activity of the leukocytes and increase their pro-inflammatory effects.…”
Section: Discussionmentioning
confidence: 80%
“…To our knowledge, this is the first report demonstrating uremic elevation of mACE-expression in relation to pro-atherogenic behaviour of primary human monocytes or THP-1 cells. Such a potential of ACE was previously reported in animal and cell culture models but was not directly correlated with influences of uremia on human monocytes in vitro [26], [27], [28], [29]. With regards to other cell culture systems, it has been demonstrated that uremic toxins may affect oxidative burst activity of the leukocytes and increase their pro-inflammatory effects.…”
Section: Discussionmentioning
confidence: 80%
“…In order to save valuable mAbs, we used not more than 3 μg/ml of pure mAbs (or 1/20 dilution of hybridoma cell culture medium) which was found to be sufficient for coating (Fig 1C and 1D). Usually the amount of ACE immunoreactive protein was estimated using the strongest mAb to ACE, clone 9B9 [16, 20], while a pattern of ACE activity precipitation by a panel of mAbs to different epitopes on ACE—conformational fingerprint of ACE—was used for the estimation of local conformational differences in ACE surface topography due to disease [5, 7, 21] or due to tissue origin of ACE [5, 9, 10].…”
Section: Resultsmentioning
confidence: 99%
“…Relative precipitation of ACE by strong mAbs (9B9, 2B11, 3A5, 2H9) dramatically differed compared to precipitation by weak mAbs (i1A8, 3G8, 1E10, and 3F11), likely reflecting difference in their affinity to ACE (Fig 7A). We should mention that some mAbs demonstrated anti-catalytic effect on ACE in solution at μg/ml concentrations [6, 15], whereas in the enzyme immunocapture assay (at an order lower concentrations the anti-catalytic effect did not exceed 20% (S1 Fig in [7]) in comparison with 10-fold differences in fluorescence signals demonstrated by ACE precipitated by different mAbs, weak and strong (Fig 7A). Therefore, we can consider anti-catalytic effect of some mAbs in this format as negligible.…”
Section: Resultsmentioning
confidence: 99%
“…First of all, we demonstrated that the binding of some mAbs was extremely sensitive to local changes in ACE conformation-due to local denaturation or inactivation, binding of ACE inhibitors or antibodies to ACE, or due to several diseases [34,39,40,[43][44][45].…”
Section: Generation Of Monoclonal Antibodies To Human Acementioning
confidence: 97%
“…It turned out that the conformationally altered ACE is characterized by an increased (up to 4 times) activity with respect to the natural substrate angiotensin I, less efficiently inhibited by a specific ACE inhibitor enalaprilat (tripeptide analogue widely used as an antihypertensive agent) and practically was not inhibited by another ACE inhibitor-nonapeptide teprotide. We also analyzed a large sample of blood plasma from healthy donors [48] and patients without uremia [62] and found eight cases of the same conformationally altered ACE as with uremia-which are less susceptible to specific ACE inhibitors [45]. Thus, patients with such conformationally altered ACE in their blood should probably be given more intensive therapy with ACE inhibitors, or replace them with antihypertensive agents of another class.…”
Section: Lungmentioning
confidence: 99%